Factors determining behavioral intentions to use Islamic financial technology Three competing models - Darmansyah, - (Emerald Publishing Limited, 2020)
Purpose The purpose of this paper is to investigate the influential factors on behavioral intentions toward Islamic financial technology (FinTech) use in Indonesia, for all types of FinTech services as follows: payments, peer to peer lending and crowdfunding.